1988
DOI: 10.1093/oxfordjournals.jbchem.a122561
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Accumulation of Pyrophosphate during Acetate Metabolism1

Abstract: Accumulation of pyrophosphate induced by acetate administration was investigated in rat liver in situ and in perfused rat liver. Intraperitoneal injection of acetate into rats increased the pyrophosphate concentration in the liver to about 2 mumol/g liver, which was 200 times that in control liver. Perfusion of liver with acetate alone did not result in accumulation of pyrophosphate. However, the further addition of a Ca2+-mobilizing hormone, such as noradrenaline or angiotensin II, together with glucagon to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Elevated acetate concentrations were shown to cause an influx of divalent cations, Ca 2+ and Mg 2+ into the liver mitochondria forming precipitates in the presence of 2 mM CaMgPPi. This process of rapid formation of complexes of CaMgPPi within the mitochondria is only compatible with the formation of the mitochondrial permeability transition pore provided that an opening of a calcium ion channel and activation of protein kinase A also occurs (Yamada et al, 1988). Beavis and Garlid demonstrated that depletion of Mg 2+ from the mitochondria matrix causes the formation of the unregulated mitochondrial permeability transition pore (Beavis and Garlid, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated acetate concentrations were shown to cause an influx of divalent cations, Ca 2+ and Mg 2+ into the liver mitochondria forming precipitates in the presence of 2 mM CaMgPPi. This process of rapid formation of complexes of CaMgPPi within the mitochondria is only compatible with the formation of the mitochondrial permeability transition pore provided that an opening of a calcium ion channel and activation of protein kinase A also occurs (Yamada et al, 1988). Beavis and Garlid demonstrated that depletion of Mg 2+ from the mitochondria matrix causes the formation of the unregulated mitochondrial permeability transition pore (Beavis and Garlid, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In man, blood acetate can reach as high a level as 1.5 mM when consuming variable quantities of alcohol (Chen et al, 2009; Lundquist, 1962). It is therefore possible under certain hormonal conditions (Yamada et al, 1988), pore opening could occur during ethanol consumption and its metabolism in man. It is therefore possible that the ability of acetate to form the mitochondrial permeability transition pore, may under certain conditions, account for some ethanol related cerebral pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…They have indicated that PPi is almost entirely intramitochondrial, and that treatment with glucagon and vasopressin increases the PPi concentration to 4 times that in control cells. In acetate metabolism, PPi is formed in both the cytosol and the mitochondria (Aas & Bremer, 1968; Barth et al, 1971), but and we (Yamada et al, 1988) also suggested that PP1 accumulated mainly in mitochondria. Under physiological conditions, mitochondria are not regarded as very important organelles in the regulation of cytosolic Ca2" (Somlyo et al, 1985;Carafoli, 1987), because of their low-affinity uptake system for the ion.…”
Section: Introductionmentioning
confidence: 61%
“…Acetate + ATP + CoA -+ acetyl-CoA + AMP + PP, Intraperitoneal injection of acetate into starved rats has been reported to increase the PP, concentration in the liver to more than 100 times that in normal liver (Veech et al, 1986;Veech & Gitomer, 1988). In a previous paper we reported that a high intracellular level of Ca2`caused by the synergistic actions of Ca2+-mobilizing hormones, such as noradrenaline, and glucagon is indispensable for the accumulation of PPi in perfused rat liver (Yamada et al, 1988). This observation is consistent with the findings that the accumulation of PP, was much less in fed animals (Veech et al, 1980(Veech et al, , 1986 & Gitomer, 1988; T. Inoue, unpublished work), and that isolated hepatocytes accumulated PPi in the presence of a Ca2ì onophore .…”
Section: Introductionmentioning
confidence: 95%
“…In liver, the mPTP is opened by a decrease in the ATP/ADP × Pi ratio subsequent to the metabolism of short‐chain fatty acids, and results in a massive uptake of CaMgPPi within the mitochondrial matrix (9, 10). Opening of the mPTP and intramitochondrial accumulation of CaMgPPi is facilitated by the presence of calcium mobilizing hormone and cyclic AMP (11). When TBI causes mPTP opening, acute cell death or initiation of slower cell death by apoptosis is likely to follow.…”
Section: Pathophysiologymentioning
confidence: 99%